Causes of Death Among Prostate Cancer Patients Aged 40 Years and Older in the United States - Ye, Yuzhong; Zheng, Yongqiang; Miao, Qi; Ruan, Hailong; Zhang, Xiaoping (Frontiers in Oncology, 2022)
Purpose: Little is known about the detailed spectrum of cause of death associated with prostate cancer (PCa). This study systematically characterized cause of death among patients with PCa. Methods: Patients with primary PCa were identified from the Surveillance, Epidemiology, and End Results program. Mortality rates were estimated. Standardized mortality ratios (SMRs) of non-cancer deaths were calculated to evaluate the risk of death and to compare with the cancer-free population. Results: This study included 1,171,149 patients with PCa. There were 501,398 deaths in total, of which only 27.4% were due to PCa, and 57.0% were due to non-cancer causes. Non-cancer deaths increased over time from 1975 to 2016, and index-cancer death decreased continually. The risk of non-cancer death was 1.45 times (SMR, 1.45; 95% CI, 1.45-1.46) that of the general population. Cardiovascular disease was the most common non-cancer cause of death, accounting for 30% of all PCa deaths. Alzheimers disease (SMR, 3.92; 95% CI, 3.85-4.00) had the highest risk of death. The mortality rate and SMR of non-cancer deaths increased with increased follow-up after diagnosis. Conclusion: Instead of the index cancer, non-cancer comorbidities are the first leading cause of death among patients with PCa, and the risk of non-cancer deaths of PCa patients was much higher than that of the general population. Clinicians and researchers should be aware of this trend to conduct timely and targeted interventions.